ASAS ITIKAD BAIK DALAM KONTRAK KERJASAMA KEGIATAN PERTAMBANGAN DI INDONESIA - Teresia Dweyana Resa; Achmad jaka Santos Adiwijaya; Ujang Bahar (JURNAL ILMIAH LIVING LAW, 2020)
Every human being has a variety of interests both individuals and the interests of the group, of course, to fulfill these interests is required of other human relationships or deeds. One manifestation of human relations is carried out through a conshelf or agreement, in particular cooperation agreements. This research aims to determine the application of the principles of goodwill in the contract of cooperation in mining activities in Indonesia, how the termination of unilateral agreements and how the agreement related to the cooperation with the law Mining in Indonesia.This research uses empirical approach methods. This empirical approach is used in the hopes of being able to obtain a clear and intact picture of the background and the intricacies of the implementation of contractual agreements and also to know the constraints faced in the implementation of the agreement The. Data collection techniques and Data collection tools using observational techniques that are data collection techniques by viewing or observing directly on the research object. Documentation technique is a technique of collecting data obtained from documents that are in the form of archives or other manuscripts obtained from institutions related to research. The research object is the parties who do the cooperation agreement on mining activities in Indonesia (case study of Supreme Court decision No. 2478 K/PDT/2014)